HUBUNGAN KEMAMPUAN SENAM DENGAN KEMAMPUAN KOGNITIF PADA SISWA KELOMPOK B TK KEMALA BHAYANGKARI I SURABAYA - Insani, Aulia (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2019)
Gymnastics ability is useful and necessary capability children in their everyday lives. But in modern timeswith various forms of technological advancements, as now, most children choose to spend a lot more timeto play in a way that facilities are available, compared to an activity that should be moving a muscle.Cognitive abilities in children are also very important because it can hone accuracy, ability to think andsolve problems. This study aims to determine the relationship of exercise with cognitive skills in studentskindergarten group B Kemala Bhayangkari I Surabaya. This study aims to determine the relationship ofexercise with cognitive skills in students kindergarten group B Kemala Bhayangkari I Surabaya. Thisresearch was conducted using quantitative research methods. In this study took a sample of 31kindergarten students in group B Kemala Bhayangkari I Surabaya. Data was collected using observationand study documentation. The technique of data analysis is product moment. Results of data analysis areknown to result count r is 0.213. At the 5% error level, then the price of the table r = 0.355. r count islower than r table so as to have low in view of the interpretation of the interpretation table r value. It canbe concluded that there is no relationship gymnastics skills with cognitive skills in students kindergartengroup B Kemala Bhayangkari I Surabaya.